2009
DOI: 10.1071/zo08068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation within species of the nematode genus Cloacina (Strongyloidea:Cloacininae) parasitic in the stomachs of rock wallabies, Petrogale spp. (Marsupialia:Macropodidae) in Queensland

Abstract: Four morphospecies of Cloacina, parasitic nematodes in the stomachs of rock wallabies (Petrogale spp.) from Queensland, were compared genetically using sequence data of the two internal transcribed spacers of nuclear ribosomal DNA (rDNA). The results suggest that two geographically isolated populations of C. ernabella from P. purpureicollis were genetically distinct. Based on the autapomorphic species concept, these two C. ernabella populations represented different species. For the three other nematode morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…rDNA (Chilton et al, 1997b(Chilton et al, , 2009). However, given the extensive diversity of cloacinine nematodes, it is possible that rDNA alone may not always meet the challenges of estimating interrelationships, particularly the cryptic species among various cloacinine nematodes.…”
Section: Speciesmentioning
confidence: 97%
See 3 more Smart Citations
“…rDNA (Chilton et al, 1997b(Chilton et al, , 2009). However, given the extensive diversity of cloacinine nematodes, it is possible that rDNA alone may not always meet the challenges of estimating interrelationships, particularly the cryptic species among various cloacinine nematodes.…”
Section: Speciesmentioning
confidence: 97%
“…Genotype Length (bp) Polymorphism G + C content Pairwise distance A high sequence variation within individuals of some Cloacina species from W. bicolor was observed (see Tables 2 and 3). A number of previous studies (Chilton et al, 2009Tan et al, 2012) have reported intraspecific variation in DNA sequences of the ITS-1 and/or ITS-2 within several species of the genus Cloacina spp. (ITS-2 2%), Hypodontus macropi (ITS-2 0.1-28%) and Macroponema comani (ITS-1 1.7 and ITS-2 2.3%) from macropodid hosts; however, that found in the present study was higher (except H. macropi) in C. eos (0.3-3.4% for ITS-1; 0.9-4.8% for ITS-2), C. edwardsi (0.8-1.3%; 0.9-2.3%), C. papillatissima (8.5%; no variation) and C. wallabiae (0.3-3.3%; 0.4-3.0%).…”
Section: Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear precedent for cryptic species in strongylid nematodes of macropodid marsupials. A number of previous studies have discovered cryptic species and/or proposed adaptive speciation [13,23,24,[30][31][32][33]. For example, Huby-Chilton et al [31] used a mutation scanning-sequencing approach to detect 5.2% sequence variation in ITS-2 between two forms of Zoniolaimus mawsonae (Nematoda: Strongyloidea) from M. rufus and concluded that they represented sibling species.…”
mentioning
confidence: 97%